Change in Motor Function and Adverse Health Outcomes in Older African Americas - Buchman, Aron S. (Exp Gerontol, 2015)
OBJECTIVE: We tested whether declining motor function accelerates with age in older African Americans. METHODS: Eleven motor performances were assessed annually in 513 older African Americans. RESULTS: During follow-up of 5 years, linear mixed-effect models showed that motor function declined by about 0.03 units/yr (Estimate, −0.026, p<0.001); about 4% more rapidly for each additional year of age at baseline. A proportional hazard model showed that both baseline motor function level and its rate of change were independent predictors of death and incident disability (all p’s <0.001). These models showed that the additional annual amount of motor decline in 85 year old persons at baseline versus 65 year old persons was associated with a 1.5-fold higher rate of death and a 3-fold higher rate of developing Katz disability. CONCLUSIONS: The rate of declining motor function accelerates with increasing age and its rate of decline predicts adverse health outcomes in older African Americans.